A single amino acid substitution (D1441Y) in the carboxyl-terminal propeptide of the proα1(I) chain of type I collagen results in a lethal variant of osteogenesis imperfecta with features of dense bone diseases. Issue 1 (1st January 2002) - Pace, J M; Chitayat, D; Atkinson, M; Wilcox, W R; Schwarze, U; Byers, P H
Abstract : Osteogenesis imperfecta (OI) is characterised by brittle bones and caused by mutations in the type I collagen genes, COL1A1 and COL1A2 . We identified a mutation in the carboxyl-terminal propeptide coding region of one COL1A1 allele in an infant who died with an OI phenotype that differed from the usual lethal form and had regions of increased bone density. The newborn female had dysmorphic facial features, including loss of mandibular angle. Bilateral upper and lower limb contractures were present with multiple fractures in the long bones and ribs. The long bones were not compressed and their ends were radiographically dense. She died after a few hours and histopathological studies identified extramedullary haematopoiesis in the liver, little lamellar bone formation, decreased osteoclasts, abnormally thickened bony trabeculae with retained cartilage in long bones, and diminished marrow spaces similar to those seen in dense bone diseases such as osteopetrosis and pycnodysostosis. The child was heterozygous for a COL1A1 4321G→T transversion in exon 52 that changed a conserved aspartic acid to tyrosine (D1441Y). Abnormal proα1(I) chains were slow to assemble into dimers and trimers, and abnormal molecules were retained intracellularly for an extended period. The secreted type I procollagen molecules synthesised by cultured dermal fibroblasts were overmodified along the full length but had normal thermal stability. These findings suggest that the unusual phenotype reflected both a diminished amount of secreted type I procollagen and the presence of a population of stable and overmodified molecules that might support increased mineralisation or interfere with degradation of bone.